Direct Assessments of the Antioxidant Effects of the Novel Collagen Peptide on Reactive Oxygen Species Using Electron Spin Resonance Spectroscopy - Kyo Kobayashi; Yojiro Maehata; Yosuke Kawamura; Masashi Kusubata; Shunji Hattori; Keisuke Tanaka; Chihiro Miyamoto; Fumihiko Yoshino; Ayaka Yoshida; Satoko Wada-Takahashi; Tomoko Komatsu; Shun-Suke Takahashi; et al. (Elsevier, 2011)
Abstract.: In the present study, we evaluated the antioxidant effects of a pepsin-treated novel collagen peptide (P-NCP) on reactive oxygen species (ROS) such as hydroxyl radical (HO•), superoxide anion radical (O2•-), and singlet oxygen (1O2), and the effects on cell viability after ultraviolet ray (UV) irradiation of human fibroblasts. We confirmed, using electron spin resonance, that P-NCP directly inhibited HO• and 1O2. Furthermore, addition of P-NCP to fibroblasts inhibited cell death induced by UVA (400 - 315 nm) irradiation in a dose-dependent manner. In addition, the antioxidant effect on 1O2 was observed in the peptide fractions rich in Gly, Pro, Hyp, Glu, Ala, and Arg. We found that Gly, Hyp, Glu, and Ala directly scavenged 1O2. These results indicated that a peptide sequence including Gly, Hyp, Glu, and Ala could play a key role in the antioxidant effects of P-NCP on 1O2. It was suggested that P-NCP can inhibit photo-aging related to ROS owing to its antioxidant effects. Keywords:: singlet oxygen, hydroxyl radical, photo-aging, human fibroblast, ultraviolet ray A (UVA) irradiation